Adsorption of Nisin on Montmorillonite: A Concentration Strategy. Issue 2 (3rd June 2016) - Ibarguren, Carolina; Audisio, M. Carina; Sham, Edgardo L.; Müller, Frank A.; Farfán Torres, E. Mónica
Abstract: The adsorption of a commercial form of nisin, Nisaplin® (Npl) (Danisco), on montmorillonite (Mt), a natural inexpensive clay mineral accepted as food additive, was assayed. The intention was to develop food grade materials capable of releasing the peptide and avoiding negative interactions that affect nisin antimicrobial activity in food environments. A set of different Mt‐Npl relation samples was prepared. The antimicrobial activity and the total organic carbon/total nitrogen (TOC/TN) content measured in nisin solutions after contact with the clay decreased as the amount of solid increased; thus, indicating the adsorption of the peptide on the support. Also, the Mt‐Npl solids presented inhibitory activity against Enterococcus faecium C1. Additionally, Fourier Transform‐Infrared Attenuated Total Reflectance spectroscopy (FT‐IR‐ATR) analysis of the Mt‐Npl lyophilised systems showed that nisin was preferably adsorbed on Mt among Nisaplin® ingredients, suggesting a unique concentration and immobilization method for this antimicrobial peptide that could be applied in food preservation. Practical Applications: Montmorillonite (Mt) is an inexpensive abundant natural clay characterized by a moderate cation exchange capacity with high surface area. Nisaplin® is a commercial form of nisin, a polypeptide bacteriocin active against several Gram‐positive food spoilage and pathogen microorganisms. The increasing demand for fresh and natural food favors the application of biopreservatives such as nisin. However, the interaction of these antimicrobials with other food components reduces their inhibitory effect when directly introduced into food systems. Thus, alternatives for the inclusion of active biomolecules in foods are necessary. Since Mt is a potential food additive, its use as a nisin immobilization agent provides a strategy to protect and optimize the gradual peptide liberation. This immobilization approach does not only offer a simple, rapid, and low cost method for the concentration of nisin, but also provides a feasible alternative procedure for the introduction of this antimicrobial peptide in food complex systems.